Comparative Antioxidant Activity of The Synthesized (E)-Chalcones - Thapa-Magar, Pradeep; Bajracharya, Najma; Upadhayay, Ganga Ram; Bajracharya, Gan B. (Journal of Institute of Science and Technology, 2024)
Depletion of dietary antioxidants has been related to rising of oxidative stress that causes chronic and degenerative diseases such as cancers, Alzheimer and aging. Therefore, finding of a readily available antioxidant is essential to offer potential chemotherapeutics. In this study, (E)-1,3-diphenylprop-2-en-1-one (1), (E)-1-(3-nitrophenyl)-3-phenylprop-2-en-1-one (2), (E)-3-(furan-2-yl)-1-(3-nitropheyl)prop-2-en-1-one (3), (E)-1-(2-hydroxyphenyl)-3-phenylprop-2-en-1-one (4), (E)-3-(furan-2-yl)-1-(2-hydroxyphenyl)prop-2-en-1-one (5), (E)-1-(2-hydroxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one (6) and (E)-3-(4-(dimethylamino)phenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one (7), that readily obtained through the Crossed-Aldol condensation between arylmethyl ketones and aromatic aldehydes, were evaluated for the antioxidant activity by using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2′-Azinobis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and Nitric oxide (NO) assays. Among the chalcones investigated, compound 7 has displayed antioxidant activity in the ABTS assay with IC50 value of 464 μM (calcd. 124 µg/mL) indicating a para-dimethylamino substitution in the B ring of chalcone enhances reduction of cationic free radical ABTS•+.